Reflections on the Constitutional Regulation of Property and Land Rights under the 2013 Zimbabwean Constitution - Tsabora, James (Cambridge University Press, 2021)
Property rights discourse, particularly the scope, nature, distribution, redistribution, recognition and protection of property rights, has dominated debate in African post-colonial property rights systems. In Zimbabwe, property rights law has been a contested space since the colonial era. That the property rights system is a contested arena is particularly so in view of the fact that colonial subjugation in Zimbabwe was characterized, in a very important way, by politically motivated land dispossession and, consequently, inequitable property rights distribution patterns. As a result, Zimbabwe's property rights law has always responded to mainstream, albeit fluid, political and economic undercurrents. This has meant that mainstream historical and contemporary debates have provided the context for understanding the constitutional regulation of property and land rights in Zimbabwe. This article assesses the constitutional regulation of constitutional property and land rights in Zimbabwe, and the conflicts and tension that are accommodated in the constitutional property rights framework.